The Leadership of Kyai in Islamic Boarding School (A Study of Islamic Boarding School in Jambi) - Kasful Kasful (State Institute of Islamic Studies Imam Bonjol Padang, 2015)
This study was conducted based on the problem of kyai leadership pattern in Islamic boarding school in Jambi which is considered as paternalistic and centralistic.  The study was aimed at exploring the effectiveness of kyai leadership at Islamic boarding schools in Jambi dealing with the following questions: 1) What kind of system is applied in the election of Islamic boarding school leader? 2) What kind of leadership model used in Islamic boarding school Jambi? 3) What is the effectiveness of the kyai leadership in relation with the vision, mission, management, and policy maker of that school? 4) What were the roles of kyai as the leader of Islamic boarding school among the society?  Qualitative design was used in this study and purposive sampling was employed to determine the respondents. Observation, interview and documentation were used to collect the data. It was found that: 1) The Islamic Boarding School of Nurul Iman applied deliberation and consensus system leader in which teachers, board of trustees and coordinator of Pecinan are participating in when electing the leader and the model of leadership in this school is charismatic.  The As'ad School leader's election was based on family-tree system and the model of leadership in this school was paternalistic. In PKP Al-Hidayah, the leader is elected directly by the government of Jambi province as the owner of the school. 2) In general, the model of leadership applied in Islamic boarding school in Jambi was collective-passive model because generally Islamic boarding school at Jambi are under the management of particular foundation.3) The leadership of kyai is not effective because the management system applied was not effective. 4) The role of kyai among the society ran harmoniously. Based on the research findings, democratic and open election system are recommended in Islamic boarding school leader election to respect individual right to consider leader's credibility, quality and acceptability.    Copyright © 2015 by Al-Ta'lim All right reserved